2021
DOI: 10.3389/fmars.2021.633314
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oyster Aquaculture Methods and Their Potential to Enhance Microbial Nitrogen Removal From Coastal Ecosystems

Abstract: Coastal ecosystems are impacted by excessive nutrient inputs that cause degradation of water quality and impairments of ecosystem functioning. Regulatory and management efforts to enhance nutrient export from coastal ecosystems include sustainable oyster aquaculture that removes nitrogen in the form of oyster biomass and increases particulate export to underlying sediments where increased organic material may enhance microbial denitrification. To better understand the impacts of oyster aquaculture on nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 94 publications
(125 reference statements)
0
2
1
Order By: Relevance
“…Desulfobacterales plays important roles in nitrogen cycling and removal, and could contribute about 12% of the genes in nitrogen pathways (Nie et al, 2021). Recently, dominant sulfate reducing microorganisms (SRM) within Desulfobacterales were also reported in the sediments of coastal oyster aquaculture ecosystems (Mara et al, 2021). The proportional abundance of Actinobacteriota (1.3%) in this study was obviously lower than that in other studies, in which it was reported up to 5%-20% (He et al, 2017;Yu et al, 2018).…”
Section: Discussioncontrasting
confidence: 61%
“…Desulfobacterales plays important roles in nitrogen cycling and removal, and could contribute about 12% of the genes in nitrogen pathways (Nie et al, 2021). Recently, dominant sulfate reducing microorganisms (SRM) within Desulfobacterales were also reported in the sediments of coastal oyster aquaculture ecosystems (Mara et al, 2021). The proportional abundance of Actinobacteriota (1.3%) in this study was obviously lower than that in other studies, in which it was reported up to 5%-20% (He et al, 2017;Yu et al, 2018).…”
Section: Discussioncontrasting
confidence: 61%
“…Moreover, in this study, the nasA , narG , and napA genes were also observed ( Figure 10 B), along with the with dominant narG gene. It is known that the NarG encodes for membrane-bound nitrate reductase, 99 which has previously been found to be high in sediments from oyster farms 100 and appears to be dominant in eastern oysters, regardless of ploidy. The higher abundances of nosZII and narG, relative to 16S genes in eastern oysters using the QMEC method are shown in Figure 10 C.…”
Section: Resultsmentioning
confidence: 99%
“…As the S/N ratio decreased, the abundance of Chromatiales and Bradymonadaceae decreased. Genera and species affiliated with these two families are SOB known to utilize the accumulated sulfides, or thiosulfates using nitrate as an electron acceptor [26]. On the other hand, Trueperaceae, Alphaproteobacteria, Desulfobacteraceae, and Vibrionaceae showed significant increases.…”
Section: Microbial Composition In Stages II and Iii With Different S/...mentioning
confidence: 99%